A DIFFERENT VARIANTS OF PRIMARY PROGRESSIVE APHASIA: A CASE SERIES - Putra, Davy; Ulita, Paulina Thiomas (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Introduction: The primary progressive aphasias (PPA) are a group of disorders consisting of logopenic (lvPPA), semantic (svPPA), and nonfluent/agrammatic (nfvPPA) variant PPA. Although it is being diagnosed with increasing frequency, PPA is still a rare syndrome. The PPA syndrome arises when the language-dominant (usually left) hemisphere becomes the principal target of neurodegeneration. It is often difficult to identify the underlying neurodegenerative disease etiologies for patients with progressive speech disorders. Here we report on 4 cases of Primary Progressive Aphasia of different variants. Case Presentation: Three patients in their fifties with PPA in logopenic, non-fluent, and semantic variants while 1 other patient aged seventy-two suffered from logopenic variant of PPA. All four of them had the insidious onset and gradual progression of a language impairment as initial complaints. Neuroimaging studies revealed cortical atrophy in various degrees and located primarily in the left side. Discussion: The PPA syndrome is diagnosed when 3 criteria are met. The patient should have the insidious onset and gradual progression of aphasia. Aphasia should initially arise as the primary impairment and constitute the principal factor underlying the disruption of daily living activities and diagnostic testing should point to a neurodegenerative, and therefore progressive, process as the only underlying cause. Three patients had early onset dementia with aphasia as the initial symptoms for all of them. We classified the patients into each variant through a diagnostic framework. The underlying pathology of our patients suggests either Alzheimer’s disease or of the frontotemporal dementia pathologies. Keywords: Logopenic, Nonfluent, Primary progressive aphasia, Semantic